Reseña de: Astigarraga, Jesús, A Unifying Enlightenment. Institutions of Political Economy in Eighteenth-Century Spain (1700-1808) - Paiva, Roberto (Espacio Tiempo y Forma. Serie IV, Historia Moderna, 2023)
Reseña de: Astigarraga, Jesús, A Unifying Enlightenment. Institutions of Political Economy in Eighteenth-Century Spain (1700-1808), Leiden-Boston, Brill, 2021, 326 págs. ISBN: 9789004442382.